A unified method of predicting soil deformations induced by various shaped-section tunnelling in clays - Zeng, Bin; Ma, Rui; Huang, Da; Ye, Siqiao; Yang, Chao; Chai, Hejun (Frontiers in Earth Science, 2023)
A unified method of predicting soil deformations induced by general and special-section tunneling in clays is proposed. Assuming that the tunneling-induced ground loss can be divided into infinite ground loss elements, and the soil deformation induced by the overall ground loss is equal to the sum of deformation due to each unit ground loss, the soil deformation due to unit ground loss is first derived based on elasticity theory solution. The soil deformation induced by random shaped-section tunneling is then obtained by integrating along the overall ground loss distribution, and the expressions are presented in the Cartesian and polar coordinate forms, respectively. By means of several cases of single circular tunneling, the reliability of the unified method is well verified through comparing with the measured data, and the performance of this method is quantitatively evaluated against the error analysis of the predictions. Taking the double-O-tube (DOT) shield tunnel for example, the unified method is further applied to predict soil deformation induced by special-section tunneling. The results show that the shape of the surface settlement curve caused by DOT shield tunneling also presents an inverted Gaussian curve. With the increase of the soil depth, the settlement of soil above the DOT shield tunnel increases slightly first and then decreases, and the settlement trough width keeps decreasing, resulting in the change of the shape of the settlement curve from “V” to “W”.